Guidelines for pressure relief and effluent handling systems (The Institute, 1998)
Current industry, government and public emphasis on containment of hazardous materials makes it essential for each plant to reduce and control accidental releases to the atmosphere. Guidelines for Pressure Relief and Effluent Handling Systems meets the need for information on selecting and sizing pressure relief devices and effluent handling systems that will maintain process integrity and avoid discharge of potentially harmful materials to the atmosphere.